RESPON TITER ANTIBODI DAN PROTEKSI VIRUS NEWCASTLE DISEASE GENOTYPE I, II, VI DAN VII SEBAGAI VAKSIN TERHADAP INFEKSI ISOLAT VIRUS NEWCASTLE DISEASE CHICKEN/INDONESIA/GTT/11. - Indriani, Risa; Dharmayanti, NLP Indi (Perhimpunan Biologi Indonesia, 2016)
ABSTRACTThe Newcastle Disease (ND) virus causes the most important disease in chicken, and very contagiuos in poultry in many countries. In Indonesia the Newcastle Disease or is called tetelo became endemic in chicken currently, the ND virus of genotype VII caused morbidity 100% and mortality 80% in chicken. The fusion and haemaglutinin-neuraminidase protein are involved in adhesion to the surface of hert cells to antibodies. HN and F protein induced by the ND vaccines have neutralizing effects. The aim of this study was to compare the antibody level and protection of several ND vaccine genotypes (genotype I, II, VI and VII) in chicken against ND virus chicken / Indonesia/GTT/11 genotype VII. Our result showed that all genotype ND vaccines (I, II, VI dan VII) produce 100% protection in chicken from clinical and mortality, but the challenge virus excretion in chickens vaccinated with ND vaccine VII genotypes were significantly different (p <0.05) to other groups. Response of antibody in chicken vaccinated ND genotype VII show highest mean titer (GMT 122) compered other ND vaccine. In onclusion, the ND virus chicken/Indonesia/ GTT/11 genotype VII is good to be used as inactive vaccine seed, which appropriate to the field virus circulating at this time.Keywords: virus, Newcastle Disease, genotype, vaccine